"TO BE INVISIBLE IN ORDER TO BE SAFE": A QUEER VIETNAMESE AMERICAN EXPERIENCE OF SELF-PROTECTION IN OCEAN VUONG’S ON EARTH WE’RE BRIEFLY GORGEOUS (2019) - Leal Gomes, Renato Lazaro (Inventário, 2024)
This research aims to analyze the intersection of sexuality and race in the identity construction of Little Dog, the protagonist of Ocean Vuong’s novel, On Earth We’re Briefly Gorgeous (2019). Specifically, it seeks to identify how he negotiates his homosexual Vietnamese American identity through language and describes his self-protective strategies in response to the ingrained social discrimination in American society. Queer Vietnamese Americans struggle to construct their identity in the United States, as they belong to two marginalized groups: LGBTQIAP+ and immigrants. Thus, a textual analysis (Belsey, 2013) was conducted, considering culture and history in language through an in-depth exploration of textual elements. This article used the concept of reading queerly (Stockton, 2023) to explain LGBTQIAP+ narratives, combined with hybridity (Pelaud, 2011) to interpret narratives within the Vietnamese American community. Results showed that the protagonist was socially oriented to adopt self-protective measures against discrimination. Experiencing inferiority during his formative years led him to seek social invisibility and caution when approaching queer topics. Little Dog represents real-life homosexual Vietnamese Americans who learn to defend themselves due to the lack of safe spaces allowing them to fully embrace their sexuality and cultural identity.